Pemberdayaan Ibu-Ibu Rumah Tangga untuk Meningkatkan Daya Saing Produk Opak Jepit - Iramani Iramani; Tatik Suryani; Nurul Hasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
The objective of community service that is held in Kedung Rukem Village, Gresik Regency is empowerment for community that produce opak jepit for enhancing their production capacity. In addition, it is also directed to give training for mitra to perfome both income and expense records in order to enable to count their cost of good manufactured and gained profits. The methodology applied in this community service was training and mentoring. The target participants are womens who produce opak jepit and promote their products which are under nine micro small medium enterprises (MSMEs). The materials given in the training covers community empowerment through Community Partnership Program (PKM), implementation of appropriate technology (TTG) to enhance both production capacity and product quality, improvement of entrepreneurial spirit, and easy way to determine cost of good manufactured and peforming financial recording. Meanwhile, mentoring was done by visiting one by one of MSMEs and delivering guidance in operating machine, how to pack an interesting product and assisting to make income and expense records (cash flow) so that it can be known the profit gained by business womens of opak jepit. The result of this community service is improvement of sales because of product capacity improvement, product quality improvement in terms of packaging and skill in compiling income and expense records. Keywords : TTG, production capacity, product quality, simple-financial-reporting